The use of pentoxifylline in the prevention and treatment of osteoradionecrosis: Integrative review - Tavares , Gabriel Silveira Botelho; Carvalho , Matheus Carramão de; Baeder, Fernando Martins; Trindade , Claudia Perez; Magalhaes , José Cássio de Almeida; Corazza, Paola Fernanda Leal (Research, Society and Development, 2024)
Osteoradionecrosis (ORN) is a severe complication that can lead to serious complications after oncological treatment with radiotherapy in the head and neck region. ORN presents as progressive necrosis of the irradiated bone, which can cause pain, infections, pathological bone fractures and complications to masticatory function. Pentoxifylline, a synthetic derivative of xanthine, has emerged as a promising therapeutic option in the prevention and treatment of osteoradionecrosis. The objective of this research was to identify, through published articles, the use of pentoxifylline in the prevention and treatment of osteoradionecrosis. An integrative review study was carried out researching the electronic databases SCOPUS® and MEDLINE®, using the descriptors standardized by the health system (DeCS) in Portuguese and English, respectively: Osteoradionecrosis, Osteoradionecrosis; Pentoxifylline, Pentoxifylline; Radiation-protective agents. It was concluded that pentoxifylline appears as an innovative drug in the therapeutic and prophylactic approach of ORN.